The Effectiveness of Collaborative Writing Strategy (CWS) In Improving EFL Learners’ Recount Text - Fitria Tokan; Satria Agust; Benni Satria (Universitas Maritim Raja Ali Haji (UMRAH), 2023)
This study aims to determine whether Collaborative Writing Strategy (CWS) is more effective for students writing recount texts in the eighth grade at SMP Negeri 1 Bintan. The research design used in this study was quasi-experimental. The population for this study was eighth-grade students. In this population, two classes were chosen the experimental group (VIII-A) and the control group (VIII-B), each consisting of 29 students. The data for this study was taken from the pre-test and post-test scores of both groups. The data or writing scores of the students were analyzed in terms of frequency distribution, normality, homogeneity, and the T-test. Based on the result of the analysis, there were different means in the experimental group 74.35 in the post-test. The control group was 67.67 in the post-test. The t-test formula was used. Based on the result of the computation, the t-value is 2.133. Based on the result of interpolation, the critical value is 1.701. The t-value is higher than the t-table (2.133 > 1.701). It means that using the Collaborative Writing Strategy (CWS) to teach and learn to write recount texts is more effective.